PENGARUH MEDIA PEMBELAJARAN BIG BOOK DENGAN METODE DISKUSI UNTUK MENINGKATKAN KEMAMPUAN LITERASI INFORMASI SISWA KELAS IV SEKOLAH DASAR - Fajar Nur Yasin (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research aims to identify and provide empirical evidence of the influence of big book media using a model of discussion about the literacy skills of students to Class IV. The method used in this research is quasi-experimental research design with nonequivalent (pretest and posttest) control group design. Sampling using random sampling techniques. These samples included 68 students consisting of 34 students of class IVA as a control class and 34 students in grade IVC as an experimental class. The research instrument used was a test in the form of a written question in the form description you have tested the validity and reliability.The data analysis technique used is descriptive and inferential analysis techniques. The results showed that the use of media big book discussion model with an effect on the ability of information literacy